2022
DOI: 10.3390/ijerph19063257
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Scale Deposits in a Drinking Water Network in a Semi-Arid Region

Abstract: The quantity and quality of the supply of fresh water to households, commercial areas, small industries, green spaces irrigation and public and private institutions in large cities face challenges from the supply sources availability and suitable distribution network performance to the full satisfaction of the established drinking water guidelines. In Mexico, the main source of water comes from groundwater. Most of the Mexican aquifers are located in arid and semi-arid weather conditions. The groundwater’s phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the detachment of particulate manganese was found to be less in iron pipes due to their roughness compared to PVC pipes. 37 A study conducted by González et al (2022) solely focused on the physiochemical properties of water that result in CaCO 3 scale formation on PVC pipes. However, the role of the pipe surface characteristics in the scale formation process has not been discussed.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the detachment of particulate manganese was found to be less in iron pipes due to their roughness compared to PVC pipes. 37 A study conducted by González et al (2022) solely focused on the physiochemical properties of water that result in CaCO 3 scale formation on PVC pipes. However, the role of the pipe surface characteristics in the scale formation process has not been discussed.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
“…However, the role of the pipe surface characteristics in the scale formation process has not been discussed. 38 A study conducted by Ketrane and Yahiaoui (2021) showed that CaCO 3 scale forms more in the aqueous phase than on the surface of HDPE pipes. However, no mechanistic discussion is provided on the role of plastic pipes in providing nucleation sites.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%
“…This study starts with the encrustations that are present on the basal part of Cerriglio's nymphaeum, characterized by the simultaneous presence of calcium and silicon compounds, to test the effectiveness of traditional and innovative chelant agents to remove the "calcareous" encrustations. The precipitation of silicon and calcium compounds can induce the formation of hydraulic compounds that are more stable than CaCO 3 [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Humans, since their origin, have developed their existence in the environment of rivers, lakes or springs from which to obtain water. Over the course of time, taking into account its importance for the development of societies and their economy, humans have developed water purification systems that allow its consumption and have channeled it through piping systems capable of transporting water under pressure to the different urban areas [1][2][3].…”
Section: Introductionmentioning
confidence: 99%